2009
DOI: 10.1371/journal.pone.0004790
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gulf: Phytophthora and Downy Mildews Are Connected by Rare Grass Parasites

Abstract: Downy mildews and root and foliar rots caused by Phytophthora are among the most destructive plant pathogens and therefore have attracted considerable attention during the past two decades. Although it has been realized that a close phylogenetic relationship exists, so far sharp distinction has been made between the obligate biotrophic downy mildews and the hemibiotrophic Phytophthora. In the study presented here, it is shown that a continuum of character states from hemibiotrophic Phytophthora species to obli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…However, the CesA3 gene tree resulting from the ML analysis, resolves the genus Phytophthora as monophyletic, which is in agreement with the findings of Kroon et al (2004) but contradictory to other studies that resolved Phytophthora as clearly paraphyletic (Cooke et al 2000;Voglmayr 2003;G€ oker et al 2007;Runge et al 2011). Yet only shown with significant support by G€ oker et al (2007), the present analyses on the CesA3 gene sequences support the monophyly of the downy mildews (Fig 2), which was mentioned to be uncertain by Thines et al (2009).…”
Section: Discussionsupporting
confidence: 61%
“…However, the CesA3 gene tree resulting from the ML analysis, resolves the genus Phytophthora as monophyletic, which is in agreement with the findings of Kroon et al (2004) but contradictory to other studies that resolved Phytophthora as clearly paraphyletic (Cooke et al 2000;Voglmayr 2003;G€ oker et al 2007;Runge et al 2011). Yet only shown with significant support by G€ oker et al (2007), the present analyses on the CesA3 gene sequences support the monophyly of the downy mildews (Fig 2), which was mentioned to be uncertain by Thines et al (2009).…”
Section: Discussionsupporting
confidence: 61%
“…This phylogenetic placement not only favours the broad circumscription of the Peronosporaceae to include the closely related groups of Phytophthora and the downy mildews (Göker et al 2007, Thines 2009) as supposed in Thines et al (2009b), but also the inclusion of the genera Halophytophthora s.str. and Phytopythium , which are morphologically similar to Phytophthora , for avoiding an inflationary introduction of family names within the Peronosporales .…”
Section: Discussionmentioning
confidence: 76%
“…Molecular phylogenetic reconstructions (Riethm€ uller et al 2002;Hudspeth et al 2003;Thines et al 2008) have revealed that obligate biotrophy has evolved independently in the WBR and the downy mildews (DM). The DM appear to be relatively late branching within the Peronosporomycetidae, apparently arising from within Phytophthora, with some genera exhibiting Phytophthora-like traits (Thines 2009). In contrast, the WBR have recently been shown to form an early branch of the Peronosporomycetidae (sensu Dick 2001), diverging before both the Pythiaceae and Peronosporaceae (Peronosporales sensu lato).…”
Section: Introductionmentioning
confidence: 99%